Terahertz spectroscopy of plasma waves in high electron mobility transistors - Nouvel, P.; Marinchio, H.; Torres, J.; Palermo, C.; Gasquet, D.; Chusseau, L.; Varani, L.; Shiktorov, P.; Starikov, E.; Gružinskis, V (Journal of applied physics, 2009)
We report on systematic measurements of resonant plasma waves oscillations in several gate-length InGaAs high electron mobility transistors (HEMTs) and compare them with numerical results from a specially developed model. A great concern of experiments has been to ensure that HEMTs were not subject to any spurious electronic oscillation that may interfere with the desired plasma-wave spectroscopy excited via a terahertz optical beating. The influence of geometrical HEMTs parameters as well as biasing conditions is then explored extensively owing to many different devices. Plasma resonances up to the terahertz are observed. A numerical approach, based on hydrodynamic equations coupled to a pseudo-two-dimensional Poisson solver, has been developed and is shown to render accurately from experiments. Using a combination of experimental results and numerical simulations all at once, a comprehensive spectroscopy of plasma waves in HEMTs is provided with a deep insight into the physical processes that are involved.